PERLINDUNGAN HUKUM BAGI KREDITUR DALAM PENYELESAIAN SENGKETA UTANG PIUTANG YANG BERUJUNG PADA KEPAILITAN DI KOTA MEDAN - Andrean Syah Putra (YAPEKAM, 2025)
This Bankruptcy Law is designed to provide legal certainty and a fair mechanism in resolving debt disputes. One of the main objectives of this Law is to protect creditors' rights by ensuring that the bankruptcy process is transparent and accountable. In addition, this Law also provides opportunities for Creditors to restructure their debts through the Debt Payment Suspension (PKPU) process, which can provide a better solution than bankruptcy. Capital articles are defined as activities related to public offerings and securities trading. This research method is normative juridical which will explore various secondary literature consisting of legislation, regulations, books, journals and papers related to Patents. The author uses the normative juridical method because the target of this research is law and rules. The definition of rules includes, legal principles, rules in the narrow sense and concrete legal regulations. This normative juridical research method aims to find coherent truth through deductive thinking. Deductive thinking. Conclusion in the study entitled legal protection for creditors in resolving debt disputes that lead to bankruptcy in the city of Medan, Before a bankruptcy decision is made by the court, a debtor cannot be declared bankrupt. If the curator commits a crime, such as forgery of letters or sale of bankrupt assets underhand, criminal sanctions can be imposed in accordance with the criminal act committed.